Decomposição térmica do ácido oleico na presença de sais de ferro para obtenção de biocombustíveis e outros produtos de interesse industrial - Fabiano Gomes Ferreira de Paula (2019)
In this work, the thermal decomposition of oleic acid (OA) wasinvestigated in the presence of iron compounds, in order to obtain biofuels and other high added-value products. For such, iron and OA based precursors were prepared and thermally decomposed at 550°C for 1h in argon atmosphere. Concerning the results, in chapter 3, precursors were prepared by mixing OA and iron(III) nitrate in molar ratios of 1:1 and 1:3 Fe:OA. After thermal decomposition the liquid products (51%wt) were composed by fatty nitriles, with 80% selectivity (for 1:3 precursor), and ketones. The solid products were mainly iron oxides, mainly magnetite, and carbonaceous materials. For last, H2 (65-73%) and light hydrocarbons C1-C4 (22-31%) were found in the gas products. In chapter 4, it was evaluated the anion effect by using iron(III) chloride as iron source for the precursor preparation. In this case, the liquid products showed the formation of acyl chlorides, but the complete conversion of OA was only achieved when Fe excess was used in the precursor preparation (Fe:0.5OA). The solid was formed by iron(II) chloride showing that the metal was reduced during the reaction, and carbon. For the gases, the same trend of chapter 3 was found, H2 (42-56%) and light hydrocarbons C1-C4 (42-58%) as major products.In chapter 5, iron oleate was synthetized as model complex for thethermal decomposition. A complete conversion of the starting acid wasachieved with 94% selectivity for ketones within the liquid fraction (55%wt). This product is used as biofuels precursors in biorefineries. The solid and gas products followed the tendency of last chapters. Afterwards, preliminary experiments were performed using Fe-rich tailings from mining industry. The promising results showed that complete conversion of OA to ketones can be achieved by using Ar pressure of 10 bar in 350°C.